1965
DOI: 10.1128/aem.13.3.443-446.1965
|View full text |Cite
|
Sign up to set email alerts
|

Microbial Degradation of Isopropyl-N-3-Chlorophenylcarbamate and 2-Chloroethyl-N-3-Chlorophenylcarbamate

Abstract: KEARNEY. Microbial degradation of isopropyl-N-3-chlorophenylcarbamate and 2-chloroethyl-N-3-chlorophenylcarbamate. Appl Microbiol. 13:443-446. 1965.-Microbial degradation of isopropyl-N-3-chlorophenylcarbamate (CIPC) and 2-chloroethyl-N-3chlorophenylcarbamate (CEPC) was observed in a soil perfusion system. Degradation in perfused soils, and by pure cultures of effective bacterial isolates, was demonstrated by the production of 3-chloroaniline and the subsequent liberation of free chloride ion. Identified isola… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
18
0
2

Year Published

1967
1967
2015
2015

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 72 publications
(21 citation statements)
references
References 10 publications
(14 reference statements)
1
18
0
2
Order By: Relevance
“…Hydrolysis of the herbicide Swep (methyl-N-(3,4-dichlorophenyl)-carbamate) to 3,4-dichloroaniline was observed in soil [305]. Several bacterial strains were isolated by Kaufman and Kearney [306] that degraded the herbicides isopropyl-N-3-chlorophenylcarbamate (chioropropham, CIPC) and 2-chloroethyl-N-3chlorophenylcarbamate (CEPC) with formation of 3-chloroaniline.…”
Section: Hydrolysis Of Phenylamidesmentioning
confidence: 99%
“…Hydrolysis of the herbicide Swep (methyl-N-(3,4-dichlorophenyl)-carbamate) to 3,4-dichloroaniline was observed in soil [305]. Several bacterial strains were isolated by Kaufman and Kearney [306] that degraded the herbicides isopropyl-N-3-chlorophenylcarbamate (chioropropham, CIPC) and 2-chloroethyl-N-3chlorophenylcarbamate (CEPC) with formation of 3-chloroaniline.…”
Section: Hydrolysis Of Phenylamidesmentioning
confidence: 99%
“…Because of its resistance to hydrolysis and oxidation, bacterial degradation is the dominant elimination pathway in the environment (Wolfe et al 1978). It leads to the formation of the toxic intermediate 3-chloroaniline which can be mineralized further (Kaufman and Kearney 1965).…”
Section: Introductionmentioning
confidence: 99%
“…Adaptation by soil micro-organisms to herbicides such tbat subsequent applicatioas are degraded more rapidly has been demonstrated for various pbenoxyalkanoic compounds (Audus, 1951;Brownbridge, 1956;Walker, 1957;Kirkland & Fryer, 1966;Kirkland, 1967), for endotbal (Horowitz, 1966), for aminotriazole (Riepma, 1962), for dalapon (Tbiegs, 1955;Leasure, 1964) and for chlorpropham (Kaufman & Kearney, 1965). Audus (1951) and Brownbridge (1956) (see Audus, 1964), have demonstrated that such enriched soils with enhanced capacity to degrade a particular phenoxy herbicide may also show increased activity against related compounds.…”
Section: Introductionmentioning
confidence: 99%